An investigation into the knowledge a Grade one teacher uses to develop the number sense of learners with mathematics learning difficulties - Fleming, Kirsty Ann (Rhodes University, Faculty of Education, Department of Education, 2020)
Learners in South Africa continue to underperform in the international and national mathematics benchmarking tests. In the primary school, poor performance in mathematics is viewed as an indicator of limited number sense. Since the end of Apartheid, there has been a proliferation of classroom-based research that attempts to explain why learners are underperforming and find solutions to the problem. Research that seeks to explain learner underperformance attributes poor learner performance to social-economic issues, teachers' poor content and pedagogical knowledge, the complexity of the Language of Learning and Teaching, and insufficient support for learners with Mathematics Learning Difficulties (MLD). With regards to the latter, research suggests that Foundation Phase teachers are not equipped to assist learners with MLD develop their number sense. This qualitative case study aims to investigate the knowledge that an expert Foundation Phase teacher draws on, in the process of teaching, to assist learners with MLD develop their number sense. Data generated from observations and interviews with a Grade One teacher was analysed using Rowland, Turner and Thwaites' (2013) Knowledge Quartet. The study found that the participant Grade One teacher employed all four categories of the Knowledge Quartet when developing her learners' number sense. In particular, she placed strong emphasis on vocabulary development as a means of circumnavigating MLD when developing number sense in a Grade One mathematics lesson. She demonstrated knowledge of: the importance of vocabulary in learning mathematics; how to develop the learners' understanding of mathematics vocabulary (and concepts); and how to adapt her approach to support the number sense development of learners with MLD. This research has value for teacher education programmes, both pre- and in-service, as it highlights the knowledge that a Grade One teacher draws on as she develops the number sense of all her learners, including those with MLD.
Keywords: Learning disabled children -- Education -- South Africa; Mathematics -- Study and teching (Elementary) -- South Africa